Thermal Behavior and Photovoltaic Application of NiII and CoIII Complexes with Substituted o‐Iminobenzoquinone Ligands. Issue 10 (9th March 2022) - Pashanova, Kira I.; Lazarev, Nikolay M.; Kukinov, Andrey A.; Zolotukhin, Alexey A.; Kovylina, Tatyana A.; Trofimova, Olesya Yu.; Petrov, Boris I.; Piskunov, Alexandr V.
Abstract: The thermal properties and an opportunity for photovoltaic applications were studied for a series of transition metal complexes derived on functionalized o ‐aminophenols ‐ mixed‐valent Co III compounds and bis‐ o ‐iminobenzosemiquinonato Ni II complexes. TGA and DSC explored the thermal behavior of compounds in the solid state. EI‐MS established the vapor phase composition. The temperature dependences of a saturated vapor pressure were measured by the Knudsen effusion method with the weight registration of the sublimated substance. Based on the volatility study data, the thermodynamic parameters of a sublimation process were calculated. A high absorptivity distinguishes metal complexes under investigation at visible and NIR regions (i. e., vis/NIR dyes) and, thus, were tested as photosensitizers in the fabricated dye‐sensitized solar cells. The photoelectric conversion efficiency (PCE) was estimated for devices with the Ni II derivatives. The Co III complexes demonstrated the absence of photovoltaic potential. Abstract : The thermal properties were studied for a series of transition metal complexes derived on functionalized o ‐aminophenols – mixed‐valent Co III and bis‐ o ‐iminobenzosemiquinonato Ni II complexes. Metal complexes under investigation distinguished by a high absorptivity at visible and NIR regions (i. e., vis/NIR dyes) were tested as photosensitizers in the fabricated dye‐sensitized solar cells. For devices with the Ni II derivatives, it could be estimated the photoelectric conversion efficiency (PCE).